Department of obstetrics and gynecology of the Siberian State Medical University. I.N. Grammatikaty (1858—1917). To the 145th birthday - I. D. Yevtushenko; A. A. Radionchenko; Ye. M. Kharitonova (Бюллетень сибирской медицины, 2003)
The biography of an outstanding scientist, a founder of the chair of obstetrics and gynecology, an ordinary professor of the Emperor’s Tomsk University (now SibSMU) I.N.Grammatikaty, one of the creators of Russian obstetric and gynecologic literature, has been presented in this article. Here are presented materials reflecting the formation and development of the chair of obstetrics and gynecology and the main scientific achievements of the chair for the last 10 years.